The Urgency of Ulayat Land Registration in Indonesia - Taupiqqurrahman Taupiqqurrahman; Rianda Dirkareshza; Rosalia Dika Agustanti; Fareta Angelita Ichwana P (LEGAL BRIEF, 2022)
The State Constitution stipulates that the State recognizes and respects customary law community units and their traditional rights as long as they are still alive and following the development of the nation, society, and the Unitary State of the Republic of Indonesia as outlined by law. The outcomes of the second and fourth constitutional amendments and the constitution's three articles are strong evidence of the state's recognition of customary law in Indonesia. There are always issues, although customary lands are constitutionally and legally protected. Interviews are a component of this normatively-based legal research method. The formulation of the issue concerns the legal protection of indigenous peoples against ulayat rights and the urgency of registering ulayat land in Indonesia. The first conclusion of this study is that the constitution and laws protect the rights of indigenous peoples to customary land. However, the community and other parties against indigenous peoples must balance constitutional and regulatory protections. Second, it is not sufficient for indigenous peoples to recognize customary land; it must also be determined by the regional director and administered at the National Land Agency office so that administration is streamlined and information is made more accessible.